2004
DOI: 10.1091/mbc.e03-11-0794
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Cell Cycle Control in Budding Yeast

Abstract: The adaptive responses of a living cell to internal and external signals are controlled by networks of proteins whose interactions are so complex that the functional integration of the network cannot be comprehended by intuitive reasoning alone. Mathematical modeling, based on biochemical rate equations, provides a rigorous and reliable tool for unraveling the complexities of molecular regulatory networks. The budding yeast cell cycle is a challenging test case for this approach, because the control system is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
707
3
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 585 publications
(740 citation statements)
references
References 109 publications
23
707
3
7
Order By: Relevance
“…These large costs make Kar et al's method hard to generalize to more complicated cell cycle models, such as Chen et al's budding yeast cell cycle model. 9 In this paper, we have proposed to accelerate the stochastic simulation using Haseltine and Rawlings' hybrid method with a more efficient partitioning strategy. Through numerical experiments, we explored different partitioning strategies and concluded that, for certain classes of models, a reaction should be put into the SSA regime only when both of the following conditions are met: (1) the reaction has a relatively low average propensity; (2) at least one of its limiting species has a very low molecule number on average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These large costs make Kar et al's method hard to generalize to more complicated cell cycle models, such as Chen et al's budding yeast cell cycle model. 9 In this paper, we have proposed to accelerate the stochastic simulation using Haseltine and Rawlings' hybrid method with a more efficient partitioning strategy. Through numerical experiments, we explored different partitioning strategies and concluded that, for certain classes of models, a reaction should be put into the SSA regime only when both of the following conditions are met: (1) the reaction has a relatively low average propensity; (2) at least one of its limiting species has a very low molecule number on average.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cost is a much larger system of variables and reactions. If a more detailed deterministic model, such as Chen et al, 9 were to be unpacked for stochastic simulation, the complexity of the model would quickly increase as well as the central processing unit (CPU) time for simulation by Gillespie's SSA.…”
Section: Introductionmentioning
confidence: 99%
“…This is still an aspect of many models of cell biology such as models of the cell cycle [7]. And it becomes an ever increasing problem as the model and the total experimental dataset gets larger, making it more and more difficult to find the best fit.…”
Section: Integrating the System Equations After Simplifying The Enzymmentioning
confidence: 99%
“…Many biological and physiological systems are modelled by large systems of ordinary differential equations (ODEs), for example cellular electrophysiology (Noble et al 1998;Iyer et al 2004), cell cycle dynamics (Chen et al 2004), gene regulation (Vilar et al 2002), metabolism (Beard, 2005) and coupled mechano-electrophysiology (Hunter et al 1998). When solving a (possibly non-linear) system of ODEs such as these, our main interest is often a linear functional of the solution, for example: (i) the solution of a given component at a specific time t * , u i (t * ); (ii) the weighted average of some component of the solution over a given time interval; (iii) a linear functional of the derivative of a specific component of the solution; or (iv) a combination of these simple linear functionals.…”
Section: Introductionmentioning
confidence: 99%